LABIO Y/O PALADAR HENDIDO: UNA REVISIÓN (2009)
The most common congenital facial defect in the newborn is cleft lip and palate. The presentation of this anomaly could include cleft lip with or without cleft palate and isolated cleft palate. It can be syndromic or non-syndromic. The epidemiologic data indicated variations in agreement with the geographic zone and the evaluated population. In Colombia, a prevalence of 1 in 500 to 1 in 1000 newborns has been reported. It is important to understand its etiology, classification, epidemiology, the clinical features that can be present and its management prior to surgical correction and timing. The purpose of this paper was to review the different characteristics that accompany this malformation.